An analysis of factors influencing wheat flour yield - Mog, David L. (Kansas State University, 2011)
The cost of wheat is the largest input cost for a flour mill, and as a result, profitability in wheat flour milling is determined in large part by milling efficiency – i.e., the amount of flour extracted per unit of wheat milled. In this project the objective was to quantify the influence of several measurable variables on flour mill efficiency. Data was collected from two commercial milling units of similar size. Linear regression was then used to estimate the relationship between flour yield and variables measuring grain characteristics and environmental factors. The analysis suggests that increasing ambient temperature and the occurrence of downtime both have a significant negative effect on flour yield. A significant difference in flour yield efficiency was also found between the two mills.
Keywords: Flour milling; Yield; Milling efficiency; Ambient temperature; Downtime; Agriculture, General (0473); Economics, Commerce-Business (0505); Operations Research (0796)